Noise risk assessment and health surveillance in the Italian state police band musicians: A cross-sectional study - Marco MICHELAZZI; Massimiliano POMPILI; Salvatore LIRANGI; Pietro NATALETTI; Diego ANNESI; Francesco CHIRICO; Andrea MAGRINI; Fabrizio CIPRANI (GIornale Italiano di Psicologia e Medicina del Lavoro, 2024)
Introduction: The State Police Band musicians are subjected to high levels of sound exposure during rehearsals and performances. This study assesses the noise risk among these musicians, employing various measurement and calculation methodologies to understand their exposure and propose preventive measures. Methods: A cross-sectional study was conducted with authorization from the Central Health Directorate of the Italian State Police Health Service. The study population included 93 musicians, divided into Acoustically Homogeneous Groups (GAO). Phonometric and dosimetric measurements were taken on July 25-26 and October 24, 2022, in both combined and separate sections. The methodologies used included evaluations based on GAO, Recurring Week of Maximum Risk (LEX,W), and task-based daily exposure (LEX,8H). The attenuation provided by hearing protection devices (HPDs) was also assessed using the OMB method. Audiometric tests were conducted to evaluate the musicians’ hearing capabilities. Results: The results indicated that the LEX,W exceeded the exposure limit in all GAOs during the Recurring Week of Maximum Risk. Task-based daily exposure LEX,8H showed that some GAOs in both combined (trombones, euphonium) and separate sections (clarinets, trumpets, oboe, tubas, trombones) exceeded the limit value of 87 dB(A). The HPDs provided to the musicians were found to offer acceptable protection. No values exceeded the lower action peak value of 135 dB(C). Audiometric tests revealed that 28% of musicians had hearing deficits, predominantly sensorineural, with the highest incidences in the trumpet, trombone, percussion, and euphonium GAOs. Discussion and Conclusion: Task-based daily exposure assessment provided more realistic individual noise exposure values, highlighting the importance of considering the acoustic properties and size of rehearsal spaces. Larger spaces with better acoustics, such as the renovated large music hall, resulted in lower exposure levels compared to smaller practice rooms. Despite acceptable HPD attenuation, some GAOs still experienced high exposure levels, necessitating further preventive measures. Key preventive and protective measures include practicing in larger spaces, reducing the number of activities, increasing breaks, rotating musicians’ positions, and using customized HPDs. Regular phonometric surveys and adequate training and information for musicians are essential for effective noise risk management. Further research is needed to explore the impact of other health factors and improve HPD compliance among musicians.